The Study of Uropathogenicity Factors for Escherichia Coli Strains - UNGUREANU, A. (Curr Health Sci J, 2016)
Urinary tract infection (UTI) is the most common form of extraintestinal Escherichia Coli infection (E.coli), and E. coli is the most common cause of UTI.The aim of this paper is to study the uropathogenicity factors for some strains of E.coli involved in the etiology of UTI and the affiliationof urinary E.coli strains to the serogroups involved in the UTI.We studied 208 strains of E. coli from urine samples sterilely collected from patients with clinical suspicion of urinary tract infection.The study was conducted in Emergency County Hospital Craiova between 2012-2014.Out of the 208 strains of E. coli submitted to the study, 60 strains (28.84%) - MRHA with human red cells, 28 strains (13.50%) - MRHA human red cells and blood red cells MSHA with guinea pigs, and 44 strains (21.12%) - MSHA with guinea pig red blood cells; 76 strains (36.54%) - no hemagglutination. Regarding our study, 42,34% of E.coli strains presented human MRHA putting forward their potential to cause pyelonephritits. The 68 hemolytic strains (37,20%) of urinary E. coli were tested for the production of the cytotoxin, thus obtaining characteristic cytotoxic effect for 26 strains (38.20%) whereas its absence was registered in 42 strains (61.80%). E. coli O6 strains isolated from hospitalized adults are more frequently hemolytic than those isolated from the other groups and MRHA was more common in hemolytic strains of the same group O6). Mannose-resistant hemagglutination is more frequent in strains that develop HLy but do not produce CNF(Cytotoxic Necrotizing Factor), than in strains producing CNF.